1992
DOI: 10.1007/bf00040855
|View full text |Cite
|
Sign up to set email alerts
|

A new model for characterizing primary creep damage

Abstract: Primary creep damage may occur at a crack tip in steel at room temperature and below. The effect of this time-dependent damage is generally neglected. Recently developed experimental data clearly show that, for some materials, neglecting time-dependent deformation and damage may be quite nonconservative and dangerous in certain practical applications.In this paper, a new theory is developed which incorporates the effects of time-dependent damage into the crack growth and failure process. The predictive ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In cold metal forming processes, multiplication of dislocations is the dominant deformation mechanism and no grain boundary sliding takes place (Li et al, 1994;Brust and Leis, 1992). This causes voids to be nucleated around second phases (Zheng et al, 1996), normally within grains, as shown in Figures 1(e), 2(c) and (d).…”
Section: Damage Due To Ductile Void Growthmentioning
confidence: 98%
“…In cold metal forming processes, multiplication of dislocations is the dominant deformation mechanism and no grain boundary sliding takes place (Li et al, 1994;Brust and Leis, 1992). This causes voids to be nucleated around second phases (Zheng et al, 1996), normally within grains, as shown in Figures 1(e), 2(c) and (d).…”
Section: Damage Due To Ductile Void Growthmentioning
confidence: 98%
“…Another aspect of the sustained-load effect is that there can be some primary creep crack growth that can reduce the failure stress or strain capacity. Primary creep crack growth can occur at any temperature if the stresses are close to the failure stress (that is, stress-induced primary creep [112,113]). The effect of hold-time on hydrostatic testing has been a concern for decades for axial flaws in pipelines.…”
Section: Effects Of Loading Ratesmentioning
confidence: 99%
“…Although creep behavior at ambient temperature is in the form of primary creep [7,8] and the creep strain is limited [9], the room-temperature creep will affect material mechanics performance [5,6,[10][11][12]. Moreover, the creep significance will be more obvious if the stress is higher, and primary creep will occur at the stress concentration area near a crack tip [13], which will threaten the safety of structure with crack. Meanwhile, the high stress level will appear due to stress concentration in practical engineering, such as the discontinuous part of structure.…”
Section: Introductionmentioning
confidence: 97%